2014
DOI: 10.1089/jop.2013.0093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Commonly Used Mydriatics on Choroidal Thickness: Direct and Crossover Effects

Abstract: The findings of the present study revealed that tropicamide and phenylephrine cause a decrease in choroidal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 31 publications
6
46
0
Order By: Relevance
“…The OCT examination was carried out immediately after the visual acuity (VA) measurement and before dilation, as per protocol, to avoid vascular choroidal effects due to the dilating drops (Kara et al 2014). A 1050-nm wavelength light source (swept-source) optical coherence tomography device (Topcon DRI OCT; Triton) was used, scanning at 100.000 A scans/second, and providing a very clear and defined visualization of the choroid layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OCT examination was carried out immediately after the visual acuity (VA) measurement and before dilation, as per protocol, to avoid vascular choroidal effects due to the dilating drops (Kara et al 2014). A 1050-nm wavelength light source (swept-source) optical coherence tomography device (Topcon DRI OCT; Triton) was used, scanning at 100.000 A scans/second, and providing a very clear and defined visualization of the choroid layer.…”
Section: Methodsmentioning
confidence: 99%
“…A 1050-nm wavelength light source (swept-source) optical coherence tomography device (Topcon DRI OCT; Triton) was used, scanning at 100.000 A scans/second, and providing a very clear and defined visualization of the choroid layer. The OCT examination was carried out immediately after the visual acuity (VA) measurement and before dilation, as per protocol, to avoid vascular choroidal effects due to the dilating drops (Kara et al 2014). A single experienced technician, who was blinded to the identity of the subjects and was not involved in the data analysis, acquired all the images.…”
Section: Methodsmentioning
confidence: 99%
“…results. Some authors demonstrated a decrease in choroidal thickness in both the treated and fellow eyes after topical phenylephrine administration (Kara et al, 2014), whereas others have reported no change in choroidal thickness (Bajenova et al, 2012) ( Table 1.7.6.1). Similarly, reports of changes in choroidal blood flow as a result of stimulation of the sympathetic system are also equivocal with both reductions in ocular blood flow (Lanigan et al, 1988;Takayama et al, 2009) and no change in posterior eye circulation in healthy human subjects being reported (Takayama et al, 2004;Robinson et al, 1985;Schmetterer et al, 1996).…”
Section: The Autonomic Innervation Of the Choroidmentioning
confidence: 98%
“…Some studies have found that application of the non-selective muscarinic antagonist 1% tropicamide does not have any influence on choroidal thickness (Mwanza et al, 2013;Öner et al, 2016), while other authors have observed a decrease in choroidal thickness after administration of 1% tropicamide or 1% cyclopentolate (Kara et al, 2014;Yuvaci et al, 2015). Contrary to these findings, three recent studies have reported that 2% homatropine, 1% atropine and 1% cyclopentolate significantly increased subfoveal choroidal thickness Öner et al, 2016;Zhang et al, 2016 selective antagonist pirenzepine (Shih et al, 1999, Siatkowski et al, 2004Chua et al, 2006;Chia et al, 2012, Chia et al, 2016.…”
Section: The Autonomic Innervation Of the Choroidmentioning
confidence: 99%
See 1 more Smart Citation